Circuit grid approach for mobile robot path planning - Xing, Likun. (2008)
The path planning is still a challenging problem even after the past 30 years' research. A global off-line path planning algorithm based on circuit grid approach is presented in this dissertation. This approach makes it easy to find the optimal feasible path. The generated path function can combine various environmental conditions such as hazardous, jamming and broad, etc. It overcomes the shortcoming of local optimum traps in some path planners. Also, this algorithm is always converging if a feasible path does exist.